Ecological risk indices for heavy metal pollution assessment in marine sediments of Jeddah Coast in the Red Sea. Issue 16 (16th December 2022) - El Zokm, Gehan M.; Al-Mur, Bandar A.; Okbah, Mohamed A.
ABSTRACT: This study explores 20 pollution indices. The conclusions derived from them are integrated to characterise Jeddah Coast along the Red Sea with respect to eight heavy metals. The concentrations of essential metals showed ranges and average values of 3433–5883 (4472 ± 838), 483–1200 (784 ± 253), 241–532 (390 ± 109), 43.3 − 91.7 (67 ± 16) and 106–172 (141 ± 23) µgg −1 for Fe, Mn, Zn, Cu and Ni, respectively. In addition, biologically non-essential metals as chemical hazards have ranges and average concentrations of 68.3–240 (157 ± 63), 1.08–2.55 (1.72 ± 0.47) and 1.33–2.82 (1.96 ± 0.55) µgg −1 for Pb, Cd and Hg, respectively. Briefly, the recently proposed modified hazard quotient (mHQ) indicates metal toxicity in the following order: Hg> Ni > Pb > Cu > Zn > Cd. A single potential ecological risk (Ei) assessment revealed that the Hg level in the study area is the most serious of the metals (EHg ; 200.67). Accordingly, the calculated Risk index ( Ri ) pointed to 50% of the sediment samples gave a moderate potential ecological risk. According to four common approaches, which were deployed for a very long study period, unpolluted to moderately polluted areas are recognised. Based on the modified degree of contamination (mCd) and sediment pollution index (SPI), the sediments at most stations were classified as moderately polluted. Stratifying two of the most recently formulated indices based on principal component analysis and sediment toxicity guidelines, the area is considered to be moderate to considerably polluted. Referring to most of the integrated pollution indicators, we concluded that station IX is highly contaminated. Interestingly, consensus was obtained among most of the implemented indices, yielding a classification as moderately polluted with heavy metals.